(untitled) (Nordic Journal of African Studies, 2010)
Lεtε is a South Guan (Kwa, Niger-Congo) language (Lewis, 2009) spoken in only one town: Larteh, located in the southeastern part of Ghana, West Africa. The language which is underdescribed is spoken by about 8,310 people (Ghana Population and Housing Census, 2000). Constituent interrogatives are one type of interrogatives Siemund (2001) identifies across the world’s languages. Three types of constituent interrogatives are operational in Lεtε. These are focused constituent interrogatives, in-situ interrogatives, and discontinuous question-word interrogatives (Akrofi Ansah, 2009). In this paper, the formation of focused constituent interrogatives in Lεtε will be described. The formation of focused constituent interrogatives involves placing the focus marker ne after a clause-initial interrogative word/ phrase. In Lεtε, constituents that are focused are put clause-initially and followed by the focus marker, ne. In Lεtε culture, the use of focused constituent questions is constrained by age and social status.